Polymicrobial Sepsis Impairs Antigen-Specific Memory CD4 T Cell-Mediated Immunity - Sjaastad, Frances V.; Kucaba, Tamara A.; Dileepan, Thamotharampillai; Swanson, Whitney; Dail, Cody; Cabrera-Perez, Javier; Murphy, Katherine A.; Badovinac, Vladimir P.; Griffith, Thomas S. (Frontiers in Immunology, 2020)
Patients who survive sepsis display prolonged immune dysfunction and heightened risk of secondary infection. CD4 T cells support a variety of cells required for protective immunity, and perturbations to the CD4 T cell compartment can decrease overall immune system fitness. Using the cecal ligation and puncture (CLP) mouse model of sepsis, we investigated the impact of sepsis on endogenous Ag-specific memory CD4 T cells generated in C57BL/6 (B6) mice infected with attenuated Listeria monocytogenes (Lm) expressing the I-Ab-restricted 2W1S epitope (Lm-2W). The number of 2W1S-specific memory CD4 T cells was significantly reduced on day 2 after sepsis induction, but recovered by day 14. In contrast to the transient numerical change, the 2W1S-specific memory CD4 T cells displayed prolonged functional impairment after sepsis, evidenced by a reduced recall response (proliferation and effector cytokine production) after restimulation with cognate Ag. To define the extent to which the observed functional impairments in the memory CD4 T cells impacts protection to secondary infection, B6 mice were infected with attenuated Salmonella enterica-2W (Se-2W) 30 days before sham or CLP surgery, and then challenged with virulent Se-2W after surgery. Pathogen burden was significantly higher in the CLP-treated mice compared to shams. Similar reductions in functional capacity and protection were noted for the endogenous OVA323-specific memory CD4 T cell population in sepsis survivors upon Lm-OVA challenge. Our data collectively show CLP-induced sepsis alters the number and function of Ag-specific memory CD4 T cells, which contributes (in part) to the characteristic long-lasting immunoparalysis seen after sepsis.